Shiitake Lentinula edodes production on a sterilized bagasse substrate enriched with rice bran and sugarcane molasses - Rossi, I. H.; Monteiro, A. C.; Machado, J. O.; Andrioli, J. L.; Barbosa, J. C. (Soc Brasileira Microbiologia, 2003)
This investigation was performed to evaluate the biological efficiency (BE), mean mushroom weight (MMW), mean number of mushroom (MNM) and mushroom quality of Shiitake [Lentinula edodes (Berk.) Pegler] when grown on a sterilized substrate composed by sugarcane bagasse enriched with rice bran and sugarcane molasses. The proportions of rice bran were 0, 15, 20, 25 and 30% (dry weight/dry weight of bagasse); and the concentrations of sugarcane molasses were 0, 30 and 60 g/kg (dry weight/dry weight of bagasse plus rice bran). Four flushes were obtained during the production cycle, providing 3 accumulated productions which were used for production analysis. The substrate supplemented with 25 and 30% rice bran yielded the highest BE (98.42 and 99.84%, respectively, about 230 days after spawning) and MNM and initially produced a lower MMW than the substrates supplemented with 15 and 20% rice bran. Any amount of rice bran added to the sugarcane bagasse improved mushroom quality, with the best production of marketable mushrooms obtained by the addition of 15% rice bran. The largest amount of sugarcane molasses (60 g/kg) increased BE (90.3 and 23.6%, on first and second accumulated productions, respectively) and MNM and no quantity affected mushroom quality.
Keywords: Lentinula edodes; shiitake; sugarcane bagasse